Perscipience of Nurses towards Pharm D: Pre and Post Interventional Educational Study - Boban, Belsy; Aboobacker, Febitha; Hussain, Nimsha; Chandrasekhar, Dilip (Indian Journal of Pharmacy Practice)
To explore the perception of nurses about the roles and responsibilities of Pharm D’s and Clinical Pharmacists, a study on perception of nurses was conducted in a tertiary care hospital of Northern Kerala, India. A total of 50 nurses from various nursing stations were selected for the study for duration of one year. A knowledge, attitude and practice questionnaire was prepared pertaining the perception of nurses towards Pharm D’s was administered to nurses’ as pre and post-intervention phases. The intervention provided was education regarding the roles, responsibilities and activities of a Pharm D’s in a hospital. Nurses pleasantly invited us after educating and explaining them about roles, responsibilities and activities of Pharm D’s. In assessing knowledge, 15.5% and 67.5% were knowledgeable about the Pharm D course in pre and post-intervention phases respectively. The attitude of nurses towards Pharm D was found to be 40.8% in pre-intervention and 55.4% in post-intervention phases. Practice domain showed an evidence of 34.4% pre-intervention and 60.8% post-intervention with significant results. The overall study results pointed out the essentiality of Pharm D’s/clinical pharmacist in pharma care services.
Keywords: Clinical Pharmacist; Nurses; Perscipience